IMPLEMENTASI BLOCKCHAIN TERINTEGRASI ANDROID SEBAGAI IDENTITAS DIGITAL DALAM DSCUMI - Muh. Rafianto; Erick Irawadi Alwi; St. Hajrah Mansyur (LPPM Universitas Abdurrab, 2026)
Conventional digital identity systems often rely on centralized authorities that are vulnerable to data breaches and manipulation. The Developer Student Club Universitas Muslim Indonesia (DSC UMI) community requires a membership verification mechanism that is credible, secure, and preserves user privacy. This research aims to implement a decentralized digital identity system fully integrated on the Android platform using blockchain technology and Zero-Knowledge Proofs (ZKP), where the entire system logic—including blockchain interactions and cryptography—is processed independently on the client side (backendless) without dependence on intermediary servers. The development method applies a Minimum Viable Product (MVP) approach with a mobile-first architecture. The system is built on native Android using the Kotlin language, integrated with the Polygon Amoy Testnet network via the Web3j library. Authentication utilizes local biometric sensors to generate cryptographic proofs based on SHA-256 hashes without storing raw data on the server. White box testing results show that the application successfully connects to the MetaMask digital wallet, validates anti-duplication logic on the Smart Contract, and automatically issues a Soulbound Token (NFT) as legitimate proof of membership. In conclusion, blockchain integration on mobile devices is proven effective in delivering Self-Sovereign Identity (SSI) that is transparent and auditable without compromising the privacy of community member data.